Efficacy and Safety of Chinese Herbal Medicine on Ovarian Cancer After Reduction Surgery and Adjuvant Chemotherapy: A Systematic Review and Meta-Analysis - Wang, Rongyun; Sun, Qiuhua; Wang, Fang; Liu, Yuan; Li, Xiang; Chen, Tianhui; Wu, Xiaoke; Tang, Huijuan; Zhou, Mengyun; Zhang, Shuzhi; Xiao, Yun; Huang, Weijia; et al. (Frontiers in Oncology, 2019)
Background: Ovarian cancer (OvC) is a malignant tumor invade ovarian epithelium and interstitium. Reduction surgery combined with adjuvant chemotherapy is standard treatment for OvC patients, but adverse effects due to chemotherapy still remain a major problem. While Chinese herbal medicine (CHM) therapy has an unique therapeutic effect to reduce side effects of chemotherapy by boosting immune system, but the evidence of CHM to treat these OvC patients are limited. Objective: We conducted systematic review to evaluate the efficacy and safety of CHM in the treatment of OvC after reduction surgery and adjuvant chemotherapy. Method: Chinese National Knowledge Infrastructure (CNKI) and PubMed up to Dec 31st 2018 were searched to identify relevant studies. Only randomized controlled trials (RCTs) were included, there was no limitation on language of the publications. Data were extracted from all included studies and meta-analysis was performed with Review Manager 5.3. Study quality was assessed and pooled risk ratios (RR) or mean difference (MD) with 95% CIs were used to evaluate the efficacy and safety of CHM. Results: A total of 18 RCTs involving 975 participants were included. There were no placebo, no treatment and CHM alone. Compared with Western Medicine (WM) alone, CHM combined with WM (CHM-WM) significantly improved TCM syndromes and symptoms, KPS scores, CD4 counts, CA125 levels, and three-year survival rate (P<0.05). Incidences of gastrointestinal reactions, marrow depression, urinary system symptoms were significantly lower in CHM-WM group than in WM group (P<0.01). There was no significant difference in CD3 counts, CD8 counts, quality of life, liver function and peripheral neuropathy between the two groups (P>0.05). Conclusion: The systematic review indicated that CHM combined with WM is effective and safe in the treatment on OvC patients after reduction surgery and adjuvant chemotherapy. However, more high-quality and large-scale RCTs are needed to confirm the efficacy and safety of CHM intervention.